Association between diabetes overtreatment in older multimorbid patients and clinical outcomes: an ancillary European multicentre study. (9th January 2023) - Christiaens, Antoine; Baretella, Oliver; Del Giovane, Cinzia; Rodondi, Nicolas; Knol, Wilma; Peters, Mike; Jennings, Emma; O'Mahony, Denis; Spinewine, Anne; Boland, Benoit; Henrard, Séverine
Abstract: Background: Diabetes overtreatment is a frequent and severe issue in multimorbid older patients with type 2 diabetes (T2D). Objective: This study aimed at assessing the association between diabetes overtreatment and 1-year functional decline, hospitalisation and mortality in older inpatients with multimorbidity and polypharmacy. Methods: Ancillary study of the European multicentre OPERAM project on multimorbid patients aged ≥70 years with T2D and glucose-lowering treatment (GLT). Diabetes overtreatment was defined according to the 2019 Endocrine Society guideline using HbA1c target range individualised according to the patient's overall health status and the use of GLT with a high risk of hypoglycaemia. Multivariable regressions were used to assess the association between diabetes overtreatment and the three outcomes. Results: Among the 490 patients with T2D on GLT (median age: 78 years; 38% female), 168 (34.3%) had diabetes overtreatment. In patients with diabetes overtreatment as compared with those not overtreated, there was no difference in functional decline (29.3% vs 38.0%, P  = 0.088) nor hospitalisation rates (107.3 vs 125.8/100 p-y, P  = 0.115) but there was a higher mortality rate (32.8 vs 21.4/100 p-y, P  = 0.033). In multivariable analyses, diabetes overtreatment was not associated with functional decline nor hospitalisation (hazard ratio, HR [95%CI]: 0.80 [0.63; 1.02]) but was associated with a higher mortality rate (HR [95%CI]: 1.64 [1.06; 2.52]). Conclusions: Diabetes overtreatment was associated with a higher mortality rate but not with hospitalisation or functional decline. Interventional studies should be undertaken to test the effect of de-intensifying GLT on clinical outcomes in overtreated patients.